Is it time to properly examine NHS reform?. Issue 2 (1st March 2023) - Fleming, Stewart
Abstract : Recent events have left the NHS starved of funds and the immediate future does not look too bright financially either. The organisation is also suffering from low staff morale and burnout of its workforce along with ever‐increasing demand. Indeed all the pressures now facing the NHS point towards a need for far‐reaching reform.